Natural history of aortic root dilation through young adulthood in a hypermobile Ehlers–Danlos syndrome cohort. Issue 6 (24th April 2017) - Ritter, Alyssa; Atzinger, Carrie; Hays, Brandon; James, Jeanne; Shikany, Amy; Neilson, Derek; Martin, Lisa; Weaver, Kathryn Nicole
Abstract : Hypermobile Ehlers–Danlos syndrome (hEDS) is a common inherited connective tissue disorder characterized by joint hypermobility. The natural history of aortic root dilation (AoD), a potential complication of EDS, has not been well characterized in this population. We describe the natural history of aortic root size in a large cohort of patients with hEDS. A cohort of 325 patients with HEDS was identified at Cincinnati Children's Hospital Medical Center (CCHMC), including 163 patients from a previous study. Medical records were reviewed and each participant's height, weight, and aortic dimensions from up to four echocardiograms were documented. Aortic root z ‐scores were calculated using two established formulas based on age (Boston or Devereux). Overall prevalence of AoD and prevalence by age were calculated and longitudinal regression was performed. The prevalence of AoD with a z ‐score ≥ 2.0 was 14.2% (46/325) and with a z ‐score of ≥3.0 was 5.5% (18/325). No significant increases in z ‐score were seen over time for patients with multiple echocardiograms. Participants under the age of 15 years had an average decline of 0.1 standard deviations (SDs)/year. No significant change was found after 15 of age. Between the ages of 15 and 21 years, Boston z ‐scores were 0.96 higher than Devereux z ‐scores. The nearly 1 z ‐score unit difference between formulas indicates caution prior to diagnosing AoD in patients with hEDS. In light of the low prevalence and lack of progression of AoD, routine echocardiograms may not be warranted for pediatric patients with hEDS.